Is specialized palliative cancer care associated with use of antineoplastic treatment at the end of life? A population-based cohort study. (October 2018) - Skov Benthien, Kirstine; Adsersen, Mathilde; Petersen, Morten Aagaard; Soelberg Vadstrup, Eva; Sjøgren, Per; Groenvold, Mogens
Background: The use of chemotherapy in the last 14 days of life should be as low as possible. Aim: To study the factors related to the use of chemotherapy in the last 14 days of life and the factors related to concurrent antineoplastic treatment and specialized palliative care. Design: This was a population-based cohort study. The data were collected from the Danish Register of Causes of Death, the Danish National Patient Register, and the Danish Palliative Care Database. Analyses were descriptive and multivariate logistic regression. Setting/participants: Cancer decedents between 2010 and 2013 in the Capital Region of Denmark. Results: During the study period, 17, 246 individuals died of cancer and 33% received specialized palliative care. In the last 14 days of life, 4.2% received chemotherapy. Younger patients and patients with hematological cancers were more likely to receive chemotherapy in the last 14 days of life. Receiving specialized palliative care was associated with a lower risk of receiving chemotherapy in the last 14 days of life—odds ratio 0.15 for hospices and 0.53 for palliative hospital units. A total of 8% of the population received concurrent antineoplastic treatment and specialized palliative care. Female gender, younger age, and breast and prostate cancer were significantly associated with this concurrent model. Conclusion: Overall, the incidence of antineoplastic treatment in the last 14 days of life was low compared to other studies. Patients in specialized palliative care had a reduced risk of receiving chemotherapy at the end of life.